A tRNA fragment, 5′-tiRNAVal, suppresses the Wnt/β-catenin signaling pathway by targeting FZD3 in breast cancer. (10th August 2019) - Mo, Dongping; Jiang, Pan; Yang, Yining; Mao, Xuelian; Tan, Xuyan; Tang, Xun; Wei, Da; Li, Bing; Wang, Xiaoming; Tang, Li; Yan, Feng
Abstract: tRNA-derived fragments offer a recently identified group of non-coding single-stranded RNAs that are often as abundant as microRNAs in cancer cells and play important roles in carcinogenesis. However, the biological functions of them in breast cancer are still unclear. Hence, we focused on investigating whether tiRNAs could play a key role in the progression of breast cancer. We have identified 5′-tiRNA Val with significantly low expression in breast cancer tissues. The down-regulation of serum 5′-tiRNA Val was positively correlated with stage progression and lymph node metastasis. Overexpression of 5′-tiRNA Val suppressed cells malignant activities. FZD3 was confirmed to be a direct target of 5′-tiRNA Val in breast cancer. In addition, FZD3, β-Catenin, c-myc and cyclinD1 levels in 5′-tiRNA Val overexpressing cells were downregulated while APC was inversely upregulated. Moreover, 5′-tiRNA Val inhibited the FZD3 -mediated Wnt/β-Catenin signaling pathway in breast cancer cells. Finally, 5′-tiRNA Val levels differentiated breast cancer from healthy controls with a sensitivity of 90.0% and specificity of 62.7%. This is the first study to show that 5′-tiRNA Val as a new tumor-suppressor through inhibition of FZD3/Wnt/β-Catenin signaling pathway, which could be as a potential diagnostic biomarker for breast cancer. Highlights: A tRNA-Derived fragment, 5′-tiRNA Val was found to be down-regulated in breast cancer. Overexpression of 5′-tiRNA Val was found to suppress breast cancer cells malignant activities. 5′-tiRNA Val as a new tumor-suppressor through inhibition of FZD3/Wnt/β-Catenin signaling pathway. 5′-tiRNA Val as a new diagnostic marker and potential therapeutic target in breast cancer.